Penerapan Model Pembelajaran PBL Bermedia Aplikasi Wordwall Untuk Meningkatkan Kemampuan Menganalisis Teks Deskripsi Peserta Didik Kelas IX - Fahrudin Imam Nurkolis; Trinil Dwi Turistiani; Eka Lidia Ustanti (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2024)
The purpose of this study is to enhance students' capacity to use the Problem Based Learning (PBL) learning model with word wall media to assess descriptive texts with regard to student learning outcomes. Classroom Action Research (CAR), which is conducted in two cycles, is the research methodology used. Both quantitative and qualitative data analysis are employed. implemented in two cycles, with one meeting per cycle. 28 pupils in grade IX at SMPN 33 Surabaya served as the study's subjects. According to the study's findings, in cycle I, the percentage of students who analyzed descriptive texts with learning outcomes was 57.9% in the good category; in cycle II, this percentage increased to 60.5% in the fairly good category; in cycle I, student activity was 34.2% in the fairly good category, with the same results in cycle II, 34.2% in the less good category; and in cycle I, the percentage of students who were classically complete (7.9%) fell to 5.2% in the better category. Therefore, it can be said that the use of word wall media in conjunction with the Problem Based Learning (PBL) learning paradigm can enhance students' learning outcomes when it comes to analyzing descriptive texts in class IX-G at SMPN 33 Surabaya.